Instantaneous volume modulus and its application in the human tongue using the in-situ strength measurement method. (May 2021) - Liu, Zhi; Qian, Shanhua; Tang, Qichen; Cheng, Shuai; Yu, Jinghu
Abstract: It is necessary to investigate the measurement and characterization methods of the mechanical properties of the human tongue to prepare excellent properties in oral biomimetic materials. In this study, a simple in-situ strength measurement ( I-SM ) device was constructed for soft materials, and the results were estimated by the MFT-5000 test rig and the finite element analysis. The instantaneous volume modulus ( IVM ) was proposed and employed to characterize the mechanical properties of the anterior tongue, and relative factors affecting its mechanical properties were discussed. The results demonstrated that the I-SM device effectively measured the deformation properties of soft materials, and the elastic modulus obtained by the finite element analysis was mainly affected by the sample thickness. The IVM of the soft material decreased initially and then stabilized with the depth-thickness ratio. The instantaneous volume modulus of the equivalent thickness ( IVMET ) could represent the deformation characteristics of the soft material. The tongue structure and its stress state affected the IVMET, which was significantly higher at the tension state than at the relaxation state. These results provided valuable insights into the design of oral bionic materials. Highlights: The in-situ strength measurement device effectively measured the deformation characteristics of soft materials. The elastic modulus generated by the finite simulation failed to characterize the deformation with different thickness. The IVMET could characterize the mechanical properties of soft materials with different thickness. The structure and the stress state of the natural tongue affected the IVMET .